2008
DOI: 10.1167/8.9.8
|View full text |Cite
|
Sign up to set email alerts
|

Figure-ground interaction in the human visual cortex

Abstract: Discontinuities in feature maps serve as important cues for the location of object boundaries. Here we used multi-input nonlinear analysis methods and EEG source imaging to assess the role of several different boundary cues in visual scene segmentation. Synthetic figure/ground displays portraying a circular figure region were defined solely by differences in the temporal frequency of the figure and background regions in the limiting case and by the addition of orientation or relative alignment cues in other ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
52
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(59 citation statements)
references
References 51 publications
7
52
0
Order By: Relevance
“…This suggests that the stimulus differences across the four configurations were small enough to leave the strength of suppression from the center to surround unchanged. Our findings are similar to those of Appelbaum et al (2008) who measured SSVEPs to a center and surround configuration reversing at different frequencies as a function of the gap between them. They showed that the frequency-tagged response to the center, whose size was fixed, was independent of gap size, which parallels our finding that the fixed-size surround evokes similar responses in all configurations regardless of gap size in the ignored condition.…”
Section: Low-level Effectssupporting
confidence: 90%
See 1 more Smart Citation
“…This suggests that the stimulus differences across the four configurations were small enough to leave the strength of suppression from the center to surround unchanged. Our findings are similar to those of Appelbaum et al (2008) who measured SSVEPs to a center and surround configuration reversing at different frequencies as a function of the gap between them. They showed that the frequency-tagged response to the center, whose size was fixed, was independent of gap size, which parallels our finding that the fixed-size surround evokes similar responses in all configurations regardless of gap size in the ignored condition.…”
Section: Low-level Effectssupporting
confidence: 90%
“…Our choice of gap size and phase offset was based on previous research that shows that the interaction between center and surround configurations varies as a function of gap size and degree of phase offset. This interaction was greatest for abutting gratings and was negligible by a gap size of 0.2° (Xu et al, 2005;Appelbaum et al, 2008). Thus we expect a weak interaction (if any) at a gap size of 0.1°and no significant interaction at a gap size of 0.25°.…”
Section: Stimulimentioning
confidence: 76%
“…One set of theories and models posit that two adjacent regions compete for object status (Craft et al, 2007;Grossberg, 1994;Kienker et al, 1986;Sejnowski & Hinton, 1987) with the winner perceived as the object, and the loser perceived as a shapeless ground. There has been some debate regarding whether neural responses are facilitated for perceived objects (Appelbaum, Wade, Vildavski, Pettet, & Norcia, 2006;Appelbaum, Wade, Pettet, Vildavski, & Norcia, 2008;Lamme, 1995), suppressed for grounds (Likova & Tyler, 2008;Peterson & Skow, 2008;Salvagio et al, 2012;Tsotsos, Culhane, Kei Wai, Lai, Davis, & Nuflo, 1995), or whether both effects occur (Strother et al, 2012). Here, our use of retinotopic mapping and precise localization of the cortical representations of the figure and ground allowed us to provide supporting evidence for ground suppression as a mechanism behind object perception.…”
Section: Discussionmentioning
confidence: 68%
“…In the interest of brevity, we provide an overview of these methods, and reference the reader to our previous work (Ales and Norcia, 2009;Appelbaum and Norcia, 2009;Appelbaum et al, 2006Appelbaum et al, , 2008 for a more a more detailed description.…”
Section: Eeg Recordingmentioning
confidence: 99%